Influence of Learning PAI on Ramadan Fasting Experience of SMPN 176 Students Cengkareng, Jakarta Barat - Zubairi, Zubairi; Abnisa, Almaydza Pratama (Didaktika Religia, 2023)
The study entitled "The Influence of Learning Islamic Religious Education on the Practice of Ramadhan Fasting for Class VIII Students of SMPN 176 Jakarta", discusses the effect of learning Islamic Religious Education, which is the X variable, on the practice of Ramadhan Fasting for Class VIII students of SMPN 176, which is the Y variable. With a population of 216 and an error rate of 10% using the Slovin formula, the number of samples can be determined to be as many as 68. By using the descriptive method and by conducting several tests using the product moment formula, the results showed that there was an effect of learning Islamic religious education on the practice of Ramadan fasting for class VIII students of SMPN 176 Jakarta, because the positive tcount value was 148,843 greater than the ttable of 1,997, and the value of the correlation coefficient, which is classified as very good, is equal to 0.99 with an influence level of 1%. The remaining 99% is influenced by other factors. The results of this study indicate that learning PAI has a significant positive effect on the students' Ramadan fasting practices at SMPN 176 Cengkareng. Students who get good and quality PAI learning tend to be more active and committed to carrying out Ramadan fasting. Factors such as understanding religious concepts, moral values, and social support from PAI teachers have an important role in increasing students' fasting practices. This research provides practical implications for Islamic education institutions and teachers. It is hoped that this research can provide a better understanding of the importance of effective PAI learning in improving students' Ramadan fasting practices. Thus, steps can be taken to improve the quality of PAI learning and provide better support to students in carrying out the Ramadan fast.